Rendición de cuentas ante el juzgado de la familia, mujer, niñez y adolescencia, por parte de quien ejerza la tenencia del menor cuando la pensión alimenticia fijada, sea mayor al 50% de la remuneración básica unificada. - Paladines López, Maryuri Xiomara (2015)
Our country still retains an ideology of family togetherness , but we have unfortunately been engaged in legal problems concerning the provision of food, there are several aspects of that broken homes are either for lack of understanding between parents , such as migration or in some cases, have children out of wedlock, the fact that this problem especially not affect the spouses , if the children in common they have, because they mistakenly believe that when distance himself from a relationship they assume that also should be clarified for the children , which should not be the case.